Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1016/j.visres.2004.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Oculomotor control in asymptomatic and recently diagnosed individuals with the genetic marker for Huntington’s disease

Abstract: We compared oculomotor control among individuals in the early stages of Huntington's disease (HD), with that of individuals who are presymptomatic HD gene carriers (PSGC) and nongene carriers (NGC). The oculomotor testing paradigm included both traditional tests and a novel experimental procedure to assess visual scanning. Traditional tests elicited saccades, pursuit and optokinetic nystagmus (OKN). HD patients demonstrated marked delay in the initiation of volitional saccades (anti-saccade and memory-guided s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
63
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 20 publications
2
63
0
Order By: Relevance
“…Poor performance in the DSST has been reported in various psychiatric and neurological disorders like major depression [7] , dementia of Alzheimer's type [7,9] , solvent abuse [8] , Parkinson's disease [9] , alcohol dependence [10] , Huntington's disease [11] , autism spectrum disorders [12] and schizophrenia [6] . The data of our study suggest pervasive increases in oxyHb in the frontal cortex during the DSST with healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…Poor performance in the DSST has been reported in various psychiatric and neurological disorders like major depression [7] , dementia of Alzheimer's type [7,9] , solvent abuse [8] , Parkinson's disease [9] , alcohol dependence [10] , Huntington's disease [11] , autism spectrum disorders [12] and schizophrenia [6] . The data of our study suggest pervasive increases in oxyHb in the frontal cortex during the DSST with healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…84,93,94 In addition, saccadic hypometria has been documented in mildly affected HD patients. 78,[91][92][93][95][96][97][98][99] Later on in the disease, manifest patients usually begin to show more prominent slowing of saccades, as well as smooth pursuit deficits. Eventually, a reduced range of eye movements is observed with vertical saccades affected more than horizontal ones.…”
Section: Clinical Ocular Motor Findingsmentioning
confidence: 99%
“…After the participant completed the testing procedure, an interactive computerized analysis 18 of the right eye position was carried out by an experienced technician who was not aware of the results of neurologic and molecular testing. The first saccade (or sequence of saccades in the MG2 task) was identified in each trial and the correct trials were selected as those in which the first saccades were consistent with the task instructions.…”
Section: Figure 1 (A) Schematic Diagram Of the Experimental Conditiomentioning
confidence: 99%
“…In a previous study, we assessed eye movement deficits in a small sample of at-risk individuals and found that individuals prediagnostic for HD demonstrated deficits of memory guided saccades. 18 Based on those results, we emphasized measures of volitional saccades in the current battery of tests.Method. Participants were recruited through the National Research Roster for Huntington Disease Patients and Families.…”
mentioning
confidence: 99%